Efficacy of Integrated Straw Formulations on Lowland Rice Field Organic Carbon and Greenhouse Gas Emissions Using CCAFS-MOT Model in Niger State, Nigeria - Koglo, Yawovi Sena; Abdulkadir, Abubakar; Feliciano, Diana; Okhimamhe, Appollonia A. (Sciencedomain International, 2016)
Aims: This study aims to determine the short term effects during off-season of pre-wetted straw and urea incorporation on lowland rice field soil carbon sequestration and greenhouse gas emissions using climate change adaptation food security mitigation option tool (CCAFS-MOT) model. Study Design: The experiment was performed using a Randomized Complete Block Design. Place and Duration of Study: Nigeria, Niger State, Bida local Government from April to July 2015. Methodology: Integrated formulations of rice straw and urea at different rates respectively: 2, 3 and 4 t/ha and 25, 50 and 75 kg/ha were used with one check plot (C) (without straw and urea). The experiment was a Randomized Complete Block Design, and ten (10) integrated formulations (treatments) were used with four (04) replications. Each replication, was made of ten (10) plots giving a total number of forty (40) plots. The effect of treatments on the following variables; Soil Organic Carbon Density Gain per Year (SOCDG/year, kg/ha) and GHGs emissions (kg/ha) were determined in order to identify the best treatments. Data collected were analyzed using GenStat 16.2 and CCAFS-MOT 1.0 for SOC balance. Matlab 11.0 and Excel 2013 were also used for data processing and graphs. Significance and Duncan’s Multiple Range Test were performed at 95%. Results: Results indicated significance difference of treatments on each parameter evaluated. SOCDG increase is function of the quantity of straw and urea incorporated (Fpr. <0.001). Moreover, the study revealed three best treatments (T2, T4 and T5). Their responses (TR, %) to Soil Organic Carbon Density Gain per Year (SOCDG/year, kg/ha) have increased up to 43%. Potential carbon sequestration estimated by the CCAFS-MOT was about 44.4% for the improved practices identified with 0% methane emission and scanty nitrous oxide emission up to 31.3%. These results give strong evidence concerning the use of pre-wetted technique as panacea to both mitigate climate change and enhance croplands productivity and resilience to these changes in Niger State, Nigeria. Conclusion: Pre-wetted straw and urea application can help to deplete greenhouse gas emission and enhance carbon on agricultural lands. However, additional trials are needed before validation of the method under different agro ecological conditions in west African zones.